Big Shark, Little Shark, and the missing teeth - Membrino, Anna; Budgen, Tim, 1977- (2022)
While Big Shark loses another tooth, Little Shark is dolefully waiting to lose his first.
Keywords: Sharks -- Fiction; Teeth -- Fiction